IMPLEMENTATION OF OJK REGULATIONS AND SUPERVISION IN THE COLLECTION OF DEPOSIT FUNDS AT BANKS - Fikri Ramadon; Intan Mesa Juita; Maulydia Anggraini; Marina; Ruri Lerian Trisha; Tasya Putri Fadilla; Karen Amelia; Aryani; Aliyyah Oktadyta (CV. Era Digital Nusantara, 2023)
Collection of deposit funds is an important component in banking activities that supports the expansion of the financial industry by providing stability and confidence to depositors. The process of licensing and registering a bank as a body authorized to collect funds, as well as setting rules related to the interest rate period, and customer protection, are all part of the implementation of the Financial Services Authority (OJK). The purpose of this study is to examine how OJK is used and supervised when banks collect deposit funds at banks. The technique used is a literature review and analysis of regulations related to regulations and guidelines issued by the OJK to regulate and supervise the collection of deposit funds in banks.